Efficacy of climatic change on the development of two strains of stalk borer, Ostrinia nubilalis (Lepidoptera: Crambidae), treated with challenger/silica nanoparticles - Amany Ramadan Ebeid (Bulletin of the National Research Centre, 2019)
Abstract Background The European corn borer, Ostrinia nubilalis (Hüb.) (Lepidoptera: Crambidae), is an important pest that disturbs the economic yield of Egyptian crops especially the corn plant. Results We examined the rate of development of two strains (one from Sharqia Governorate and the other from Qena Governorate) treated with challenger/silica nanoparticle formulation within a range of temperatures (15 to 45 °C). The developmental period and thermal requirements (DD) of O. nubilalis at four constant temperatures (15, 25, 35, and 45 °C) were significantly different between each other. The developmental rate of both strains increased significantly with the increase of temperature. The estimated life table for both treated populations from different two localities predicted their population dynamics. Conclusion The duration and thermal requirements of two populations of the silica nanoparticle-treated strains of Ostrinia nubilalis (Hüb.) from different localities, and its development at four tested constant temperatures were significantly different between each other. Such information and life table are crucial to predict the seasonal abundance of the adult O. nubilalis in the field, which is essential for the successful implantation of control measures and enables us to determine the best time for controlling with better performance.